2008
DOI: 10.1093/nar/gkn581
|View full text |Cite
|
Sign up to set email alerts
|

The putative RNase P motif in the DEAD box helicase Hera is dispensable for efficient interaction with RNA and helicase activity

Abstract: DEAD box helicases use the energy of ATP hydrolysis to remodel RNA structures or RNA/protein complexes. They share a common helicase core with conserved signature motifs, and additional domains may confer substrate specificity. Identification of a specific substrate is crucial towards understanding the physiological role of a helicase. RNA binding and ATPase stimulation are necessary, but not sufficient criteria for a bona fide helicase substrate. Here, we report single molecule FRET experiments that identify … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
92
0

Year Published

2009
2009
2014
2014

Publication Types

Select...
5
2

Relationship

5
2

Authors

Journals

citations
Cited by 35 publications
(97 citation statements)
references
References 49 publications
5
92
0
Order By: Relevance
“…For example, the C-terminal domains of the splicing helicases CYT-19 and Mss116 mediates interactions with structured RNA (Grohman et al, 2007;Mohr et al, 2008). In contrast, the C-terminal domains of DbpA and YxiN specifically interact with a hairpin in ribosomal RNA (Diges and Uhlenbeck, 2001;Tsu et al, 2001;Kossen et al, 2002;Karginov et al, 2005;Wang et al, 2006), and the C-terminal domain of Hera provides high affinity for ribosomal RNA and RNase P RNA, among others (Morlang et al, 1999;Linden et al, 2008). The influence of domains flanking the helicase core on RNA binding and on DEAD box mechanism in general will be discussed in detail in 'Modulation of the helicase core activity by interacting partners and flanking domains'.…”
Section: Rna Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the C-terminal domains of the splicing helicases CYT-19 and Mss116 mediates interactions with structured RNA (Grohman et al, 2007;Mohr et al, 2008). In contrast, the C-terminal domains of DbpA and YxiN specifically interact with a hairpin in ribosomal RNA (Diges and Uhlenbeck, 2001;Tsu et al, 2001;Kossen et al, 2002;Karginov et al, 2005;Wang et al, 2006), and the C-terminal domain of Hera provides high affinity for ribosomal RNA and RNase P RNA, among others (Morlang et al, 1999;Linden et al, 2008). The influence of domains flanking the helicase core on RNA binding and on DEAD box mechanism in general will be discussed in detail in 'Modulation of the helicase core activity by interacting partners and flanking domains'.…”
Section: Rna Bindingmentioning
confidence: 99%
“…As a unique feature so far, this C-terminal domain is bipartite and consists of a dimerization motif , and an RBD that mediates high affinity interaction with ribosomal RNA fragments and RNase P RNA (Linden et al, 2008). Despite the lack of sequence similarity with YxiN, the Hera RBD folds into a modified RRM ).…”
Section: Modulation By Insertions and Flanking Domainsmentioning
confidence: 99%
“…8-Oxo-ATP was tested as an energy source for Hera helicase activity ( Figure 1C). Although wild-type Hera displayed ATP-dependent RNA unwinding activity on a 32/ 9mer RNA substrate derived from 23S rRNA (Linden et al, 2008), no unwinding of RNA in the presence of 8-oxo-ATP was observed. By contrast, Hera_Q28E showed no unwinding activity, neither with ATP nor with 8-oxo-ATP as the energy source ( Figure 1C).…”
Section: -mentioning
confidence: 94%
“…They are named according to the characteristic sequence of their Walker B motif, which is implicated in ATP binding. DEAD-box proteins share a common modular architecture ( Figure 1A): a helicase core of two flexibly connected RecA-like domains (RecA_N and RecA_C), which are sometimes flanked by additional domains that confer substrate binding specificity, mediate protein/protein interactions or may contribute to duplex separation (Tsu et al, 2001;Kossen et al, 2002;Grohman et al, 2007;Linden et al, 2008;Mohr et al, 2008;Del Campo et al, 2009). In addition, DEAD-box helicases can also form dimers Rudolph and Klostermeier, 2009) via dedicated dimerization domains, as has recently been found for the Thermus thermophilus at resistant NA-dependent TPase, Hera He R A (Morlang et al, 1999), a DEAD-box RNA helicase presumably involved in ribosome assembly and assembly of RNase P (Linden et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation